2021
DOI: 10.1007/978-981-16-3690-5_14
|View full text |Cite
|
Sign up to set email alerts
|

University Recommendation System for Higher Studies in USA

Abstract: With the increasing number of graduates seeking to pursue higher education, getting a student's admission into the university becomes more challenging. New graduate students are typically unaware of the postgraduate admission criteria and procedures and may spend a substantial amount of time obtaining guidance from consulting firms to help them define their admission opportunities. But this methodology can be biased and misleading considering the small number of universities that a human consultant may conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In profiling and prediction applications, three types of decisions were identified: 1) identification of students at risk of dropping out of a course, study programme, or school [20], [42], [46], [47], [49], [51]- [63], 2) prediction of student performance prior to their admission [21], [64]- [67], 3) identification of students' learning profile [43], [50], [68]. The first two types of decisions have a more significant impact on access to studies than the last one.…”
Section: Profiling and Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…In profiling and prediction applications, three types of decisions were identified: 1) identification of students at risk of dropping out of a course, study programme, or school [20], [42], [46], [47], [49], [51]- [63], 2) prediction of student performance prior to their admission [21], [64]- [67], 3) identification of students' learning profile [43], [50], [68]. The first two types of decisions have a more significant impact on access to studies than the last one.…”
Section: Profiling and Predictionmentioning
confidence: 99%
“…This type of decision has a rather low impact as it simply provides a list of courses or materials that could be of interest to students. In comparison, five articles utilised AI to recommend higher education institutions or programmes to students [21], [64]- [67]. These recommendations can potentially impact students' decision to apply to a specific programme or university, impacting their future job and salaries.…”
Section: Recommendersmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing the educational context allows directing efforts towards educational quality objectives. The commonly identified educational levels are primary, secondary, higher (da Silva et al, 2022) and postgraduate (Nalawade & Tiple, 2022), however, the U.S. educational system includes K-12 schools, the "K" refers to "Kindergarten", which is the first year of formal education, and the "12" refers to the 12 years of education that includes primary and secondary (Zayet et al, 2022). It should be noted that some ERS were implemented for 2 or more levels and the same happens with educational modalities; some articles indicated that ERS were used in 2 or more modalities.…”
Section: Machine Learningmentioning
confidence: 99%